The legal conditions of national mourning in the light of forms of public administration activities - Sierpowska, Iwona (The Opole Studies in Administration and Law, 2021)
Traditionally, national mourning is introduced to commemorate persons who have rendered outstanding services to the nation. However, over the past several years, mourning has also been announced in connection with various tragic events. This indicates an evolution of the institution and it may also raise concerns about its abuse and depreciation. The law refers to national mourning in a very general way, hence it is the practice that tries to fill in the void and eliminate deficiencies in the legislation. This leads to situations in which administrative bodies take actions which they have not been empowered to. A special problem is the delimitation between the act of introducing mourning and the act of suspending the organisation of entertainment events during its duration.